Kecemasan Orang Tua dalam Pelaksanaan Latihan Sepakbola Di Masa Covid 19 - Dini Rosdiani; Agus Santosa; Franz Hardika Agung (STKIP Paasundan Press, 2022)
The purpose of this study was to determine the level of parental anxiety in implementing soccer practice during the covid-19 period. The method used in this research is descriptive quantitative with a survey approach. The population in this study was parents of students who accompanied their children to practice soccer at the Siliwangi soccer school, Cimahi City, amounting to 20 people. The sampling technique in this study used a purposive sampling technique. The reason for using this purposive sampling technique was because researchers could only conduct research on parents aged 9-10 in SSB Siliwangi, Cimahi City. The instrument in this study used an anxiety questionnaire. The first data analysis was tested for the level of validity and reliability. The correlation coefficient (rcount) for each statement item is compared with the Pearson correlation coefficient (rtable) with the significance level used is = 0.05 or 5%. Reliability test using Cronbach's Alpha formula and the result is 0.803 from 5% significance, it is obtained rtable 0.666. Thus, it can be concluded that ri = 0.803 > rtable 0.666 then this data instrument is declared reliable. The results of statistical analysis show that the level of parental anxiety level categories in the implementation of soccer training during the Covid-19 period are (2%)